Impact of landmark identification and standard measurement error on cephalometric analysis using a mathematical simulation model - Eduardo Luiz Delamare; Gabriela Salatino Liedke; Mariana Boessio Vizzotto; Heraldo Luis Dias da Silveira; Dalva Maria Pereira Padilha; José Luis Duarte Ribeiro; Priscila Fernanda da Silveira; Heloisa Emilia Dias da Silveira (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2012)
Objective: To assess, using a mathematical simulation model, the participation of each coordinate involved in the formation of cephalometric angles and to determine the extent to which errors in the identification of cephalometric landmarks can, individually and collectively, influence the measurement of these angles. Material and Methods: The reference values and standard errors of 13 landmarks obtained from the analysis of 30 cephalograms were used. For each landmark, 1000 observations were simulated using the Monte Carlo method. On the basis of linear regression models, equations designed to estimate measurement errors due to landmark identification errors were obtained and analysed. Results: The coordinates most involved in the formation of the angles SNA, SNB, ANB, FMA, PPL, DFC, and AEF were Ny, Ny, Ax, Goy, Poy, Poy, and Ptmx, respectively, and the standard measurement errors for these angles were 1.2, 0.9, 0.8, 1.6, 1.5, 1.5, and 1.4, respectively. Conclusion: The standard measurement error of the angle depends on the geometric impact coefficient and the standard error of the coordinates involved in the formation of the angles, and the geometric impact coefficient varies according to the angle analysed.